MENINGKATKAN KOMPETENSI GURU MEMBANTU KESULITAN BELAJAR ABK DENGAN SUPERVISI AKADEMIK TEKNIK EVALUASI DIRI - Ida Ayuning Mu'arifah (JURNAL SINEKTIK, 2021)
The purpose of the research is to analyze the improvement of pedagogical competence of SDN Teacher Sukoharjo to help the learning difficulties of Children with Special Needs (ABK) with the application of academic supervision of self-evaluation techniques in the semester I of the 2019/2020 School Year. Research place in SDN Sukoharjo, Rembang Subdistrict, Rembang Regency. Research time in the beginning to the middle of Semester I of the 2019/2020 School Year. The study subjects were 10 people. Data collection techniques are non-test techniques and test techniques. Data analysis techniques are qualitative descriptive analysis techniques and comparative descriptive analysis techniques. The procedure in research is the Cycle Model. The conclusion of this study is that the pedagogical competence of teachers helps the learning difficulties of ABK with the application of academic supervision of self-evaluation techniques increased. In the Early Conditions, the pedagogical competence of teachers belongs to the category quite well with a percentage of 10%. In Cycle I, the pedagogical competence of teachers belongs to the category of good with a percentage of 70%. In Cycle II, the pedagogical competence of teachers belongs to the category of good with a percentage of 100%.